Economic Analysis of the Impact of Development Programs on Buffalo Milk Producers in the Marshes of Iraq as A model - M. Nadhim, Mowj; K. Jabara, Osama; J. Abdulradh, Mohammed (Journal of Economics and Administrative Sciences, 2025)
The research examined the impact of development programs on local buffalo milk ‎producers in the marsh areas of Iraq, focusing on productivity levels and residents' living ‎standards. Data was collected from 200 producers in the governorates of Dhi-Qar, Maysan, ‎and Basra, all participating in the development program. ‎The research assumed that the introduction of modern technologies and the provision ‎of production requirements by international organizations or government initiatives would ‎enhance the production levels and productivity of the rural population. Consequently, this ‎improvement may reflect their standard of living and strengthen their connection to the ‎land, thereby reducing migration. These individuals not only require support to maintain ‎their self-reliance without the need for future aid but also to evolve into a dynamic ‎economic force contributing to the development of the national economy.‎Using a superior logarithmic production function analyzed by the Frontier statistical ‎program, the study found that the number of buffalo and the amount of hay positively ‎affected milk production. At the same time, bran and barley had a negative impact. Technical ‎efficiency varied widely among breeders, with the highest efficiency at 0.9341 for a ‎participant breeder and the lowest at 0.2910 for a non-participant. Those adopting ‎technology had an average efficiency of 0.78 compared to 0.55 for non-adopters. The ‎findings emphasize the positive role of technology in improving efficiency and underscore ‎the need for increased adoption of these practices among producers. Furthermore, buffalo ‎breeders in the marshlands produce with low technical efficiency due to their inefficient ‎use of production resources. The study recommended increasing the use of modern ‎technologies, urging breeders to increase their use, and facilitating their adoption of this ‎technology.‎